KETERWAKILAN PEREMPUAN DALAM PENGAMBILAN KEPUTUSAN BERDASARKAN FUNGSI DPRD DI KOTA SEMARANG PERIODE 2014-2019 - Hikmia Rahadini Pradipta; Turtiantoro . (Journal of Politic and Government Studies, 2018)
Members of the legislature are individuals and groups of people who occupy the legislature (DPRD) representing the community to perform its functions. In this study the author took the title of Women Representation in Decision Making Based on the Function of Parliament in the city of Semarang period 2014-2019. The functions in question include the functions of legislation, budgeting, and supervision. Women's political participation is important for achieving gender equality in politics, women's involvement in public life has increased but their participation and representation in legislative bodies at both national and regional levels can be said to have not met the 30% quota.The problem in this research is how the involvement of women council members representatives in each commission in Semarang Council for the period 2014-2019 and what obstacles women council members get in running the function of DPRD in Semarang City Council.The research method used is qualitative research method is descriptive, research data obtained through interviews, documentation and literature study. The research location is in Semarang City Council. Informants or resource persons in this study are 5 female council members on each commission as the main subject and one male board member to represent the views from another point of view.In the legislative membership of Semarang City Period 2014-2019 there are 11 female council members who legitimately win votes in each electoral district and this is the first time the number of representatives of women in the Regional House of Representatives of Semarang City has increased significantly from periods previous. However, the eleven female council members still have not occupied important structural positions, the highest positions obtained by this female councilor as vice chairman of the commission and here there are 2 women council members who occupy that position is on commission A and commission D. While 9 (nine) other female council members are only domiciled as members of one of the commissions and other DPRD fittings, such as deliberation bodies, regulatory bodies, budget bodies and honorary bodies. Performance of women council members in making decisions in Semarang City can be seen based on their efforts in fighting for the rights and demands of the people, especially for women through policy and development. Keywords: women's representation, position, role, performance, function of DPRD